2020
DOI: 10.1111/hel.12775
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Maastricht V/Florence consensus report for the management ofHelicobacter pyloriinfection among primary care physicians and medical students in Croatia: A cross‐sectional study

Abstract: Background Helicobacter pylori (H pylori) eradication is becoming increasingly difficult. The aim of our study was to determine the knowledge of current guidelines and attitude in the diagnosis and treatment of H pylori infection in primary care physicians (PCPs) and medical students in Croatia. Materials and Methods A study was conducted among PCPs and medical students to evaluate adherence to Maastricht V consensus guidelines. Questionnaire was distributed by e‐mail to 2338 PCPs offices in Croatia and to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…H. pylori is believed to be one of the main driving forces in the progression of non-cardia gastric cancers from acute gastritis to chronic gastritis, followed by atrophic gastritis and eventually progressing to malignancy. 12 H. pylori has the characteristics of cluster reproduction and tissue-specific adsorption. H. pylori initially colonizes the mucus layer covered by the epithelium of the gastric mucosa, and then penetrates to the mucus layer and specifically adheres to the surface mucus cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori is believed to be one of the main driving forces in the progression of non-cardia gastric cancers from acute gastritis to chronic gastritis, followed by atrophic gastritis and eventually progressing to malignancy. 12 H. pylori has the characteristics of cluster reproduction and tissue-specific adsorption. H. pylori initially colonizes the mucus layer covered by the epithelium of the gastric mucosa, and then penetrates to the mucus layer and specifically adheres to the surface mucus cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the most comprehensive study assessing practice patterns of gastroenterologists and gastroenterology fellows in the diagnosis and treatment of H. pylori infection in Europe. Previous studies reported either attitudes of primary care physicians 18 or practices of gastroenterologists, but not gastroenterology fellows, with particular focus on the first‐line treatment of H. pylori 14 . Another comprehensive survey on the adherence of gastroenterologists to guideline for the management of H. pylori infection was carried out in China 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies had shown more obstacles to successful management of the disease, such as insufficient knowledge of H. pylori guidelines among primary care physician and medical students. 18 Additional problem was a poor accordance between treatment regimens and drug pack sizes. 19 Those challenges could contribute to antimicrobial resistance, affect adherence, lead to more medication errors and worse outcomes for the patients.…”
Section: Introductionmentioning
confidence: 99%
“… 19 Those challenges could contribute to antimicrobial resistance, affect adherence, lead to more medication errors and worse outcomes for the patients. 18 19 Another obstacle to improved H. pylori eradication could be the poor integration of the latest research into the practice due to insufficient reporting quality. So far, the quality of published RCT abstracts in the field of gastroenterology, the cornerstone of evidence based medicine practice, remained unknown.…”
Section: Introductionmentioning
confidence: 99%